IMPROVING MATHEMATICS LEARNING OUTCOMES IN 3RD CLASS PRIMARY STUDENTS USING THE MASTERY LEARNING MODEL THROUGH SMART LADDER MEDIA - Gatot, Masitowati; Kholishoh, Umi; Kusumawati, Naniek (Program Studi PGMI, 2024)
Mathematics for some students is still a difficult and boring lesson. The results of observations at SDN Kemuning, Sambit District, Ponorogo Regency, class 3 showed that there was a problem, that students' learning outcomes were still far from the KKM (75), in terms of length, weight and time. The aim of this research is to improve student learning outcomes in Mathematics lessons with material in units of length, weight and time, using the Mastery Learning model through the Smart Ladder media. This re-search is Classroom Action Research (PTK) with 4 stages, namely planning – implementation – observa-tion – reflection. The research subjects were 3rd grade students at SDN Kemuning Sambit with a total of 11 students. This research was conducted with 2 cycles of Completeness of Student Learning Achievement, in the pre-cycle the average score was 62 with a percentage of 18%, in the first cycle the average score was 70 with a percentage of 54%, while in the second cycle the average score was 86 with a percentage of 91 %. The results of the observation assessment on teacher activities in cycle I were 77% in the active category, while cycle II was 96% in the very active category. Meanwhile, the results of student activity assessments in cycle I were 73% with classical completeness of 73%, which was in the quite active category, in cycle II the average score was 79% with classical completeness of 86%, which was in the active category. This shows that the Mastery Learning learning model through the Smart Ladder media is very effective in learning.